Prevalence evolution of SARS-CoV-2 infection in the city of São Paulo, 2020–2021 - Albuquerque, José Olimpio Moura de; Kamioka, Gabriela Akemi; Madalosso, Geraldine; Costa, Selma Anequini; Ferreira, Paula Bisordi; Pino, Francisco Alberto; Sato, Ana Paula Sayuri; Carvalho, Ana Carolina Aguiar de; Amorim, Ana Beatriz Pagliaro; Aires, Caroline Cotrim; Kataoka, Ana Paula Arruda Geraldes; Savani, Elisa San Martin Mouriz; et al. (Revista de Saúde Pública, 2021)
OBJECTIVE To estimate the evolution of the prevalence of SARS-CoV-2 virus infection among residents aged 18 years or over in the municipality of São Paulo. METHODS This is a population-based household survey conducted every 15 days, between June and September 2020, and January and February 2021. In total, the study comprised 11 phases. The presence of antibodies against SARS-CoV-2 was identified in venous blood using a lateral flow test, Wondfo Biotech. In the last phase, the researchers combined it with an immunoenzymatic test, Euroimmun. The participants also answered a semi-structured questionnaire on sociodemographic and economic factors, and on social distancing measures. Prevalence estimates and the 95% confidence interval were estimated according to regions, Human Development Index, sex, age group, ethnicity, education, income, and variables associated with risk or prevention of infection. To compare the frequencies among the categories of each variable, the chi-square test with Rao-Scott correction was used, considering a significance level of 5%. RESULTS In total, 23,397 individuals were interviewed and had their samples collected. The estimated prevalence of antibodies against SARS-CoV-2 ranged from 9.7% (95%CI: 7.9–11.8%) to 25.0% (95%CI: 21.7–28.7). The prevalence of individuals with antibodies against the virus was higher among black and brown people, people with lower schooling and income, and among residents of regions with lower Human Development Index. The lowest prevalences were associated with recommended measures of disease protection. The proportion of asymptomatic infection was 45.1%. CONCLUSION The estimated prevalence of the infection was lower than the cumulative incidence variation, except for the last phase of the study. The differences in prevalence estimates observed among subpopulations showed social inequality as a risk of infection. The lower prevalence observed among those who could follow prevention measures reinforce the need to maintain social distancing measures as a way to prevent SARS-CoV-2 infection.